YouTube Upload Scheduling Strategy for Improving the Video Quantity and Audiences' Segmentation Accuracy at PT Talenta Entertainment - Dermawan, Paris (Journal of Indonesian Tourism and Policy Studies, 2025)
Youtube provides features for its users to upload and watch other users' videos. PT. Talenta Entertainment utilizes YouTube to upload creative videos of each talent that has been produced. In addition, in addition to the right media, creative and interesting content also needs to be distributed at the right time so that the upload time is right with the free time of the audience segment. Therefore, the content upload scheduling strategy plays an important role in finding the right time for the audience segment so that it can increase the number of views that have been uploaded. The purpose of this study was to determine the content upload scheduling strategy to increase the number of views of creative talent content at PT Talenta Entertainment. The method used is a qualitative descriptive research method with data collection techniques through interviews, observations, and literature studies. The results of this study indicate that the scheduling strategy implemented by PT Talenta Entertainment has proven to be quite significant in increasing the number of views.